2004
DOI: 10.1211/0022357023079
|View full text |Cite
|
Sign up to set email alerts
|

Anti-ulcerogenic effect of chitin and chitosan on mucosal antioxidant defence system in HCl-ethanol-induced ulcer in rats

Abstract: The anti-ulcerogenic effect of chitin and chitosan against ulcer induced by HCl-ethanol in male Wistar rats was studied. Levels of acid output, pepsin, protein, lipid peroxides and reduced glutathione and the activity of glutathione peroxidase (GPx), glutathione-S-transferase (GST), catalase (CAT) and superoxide dismutase (SOD) were determined in the gastric mucosa of normal and experimental groups of rats. A significant increase in volume and acidity of the gastric juice was observed in the ulcer-induced grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
29
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(33 citation statements)
references
References 34 publications
4
29
0
Order By: Relevance
“…Chitosan, a polysaccharide found in shellfish, krill, fungi, and insects, has membrane stabilizing properties (Filipović-Grcić et al 2001) and helps to upregulate Hsp70 expression (Khodagholi et al 2010). Chitosan was reported to be neuroprotective by suppressing Aβ formation (Khodagholi et al 2010), it can reduce age-related dyslipidemic abnormalities and oxidative stress in aged rats (Anandan et al 2013), and has anti-ulcerogenic effect against HCl-ethanol induced ulcer (Anandan et al 2004). Geranylgeranylacetone (GGA) is an antiulcer drug which protects the cells of the gastric mucosa against several forms of stress.…”
Section: Possible Mechanism Of Hsp Protection and Potential Therapeutmentioning
confidence: 99%
“…Chitosan, a polysaccharide found in shellfish, krill, fungi, and insects, has membrane stabilizing properties (Filipović-Grcić et al 2001) and helps to upregulate Hsp70 expression (Khodagholi et al 2010). Chitosan was reported to be neuroprotective by suppressing Aβ formation (Khodagholi et al 2010), it can reduce age-related dyslipidemic abnormalities and oxidative stress in aged rats (Anandan et al 2013), and has anti-ulcerogenic effect against HCl-ethanol induced ulcer (Anandan et al 2004). Geranylgeranylacetone (GGA) is an antiulcer drug which protects the cells of the gastric mucosa against several forms of stress.…”
Section: Possible Mechanism Of Hsp Protection and Potential Therapeutmentioning
confidence: 99%
“…Proponents suggest, therefore, that GlcN could be used to build bones [5]. GlcN also increases the barrier function of skin cells and stimulates intestinal epithelial cells to secrete mucin, which has an anti-ulcerogenic effect [6,7]. Because of these benefits, GlcN represents a potentially useful biologically active compound [8], and it has already been approved as a prescription drug in Europe, a food supplement in the USA, and a health food in China [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Previous reports [3,4] have shown that the dietary supplementation of chitosan is capable of ameliorating high fat diet-induced hyperlipidemia in experimental animals. Earlier Anandan et al [5] investigated the antiulcer effect of chitosan against HCl-ethanol mixture induced peptic ulcer in rats. It has been reported to possess antilipidemic [6], antioxidant [7] and membrane stabilizing properties [8].…”
Section: Introductionmentioning
confidence: 99%